Penerapan Metode Pembelajaran Quantum Teaching untuk Meningkatkan Kemampuan Menulis Puisi dengan Media Bergambar dan Audiovisual Pada Siswa Kelas IV SDN 2 Blembem - Ardianti Indah Nirmala; Endang Sri Maruti; Vivi Rulviana (Universitas PGRI Madiun, 2026)
Abstract: One of the efforts to improve the language skills of fourth grade students is through the introduction of literature in the form of poetry. However, in practice, many students still have difficulty writing poetry, so that the learning outcomes on the material have not reached the Minimum Completion Criteria (KKM). This study aims to describe the application of the Quantum Teaching method with pictorial and audiovisual media and to describe the improvement in the poetry writing skills of fourth grade students of SDN 2 Blembem, Jambon District, Ponorogo Regency. The study used a qualitative descriptive approach with the type of Classroom Action Research (CAR) which was carried out in two cycles on 11 students from March to June 2026. Each cycle consisted of planning, implementation, observation, and reflection stages, with the application of the TANDUR syntax (Grow, Experience, Name, Demonstrate, Repeat, Celebrate). Data were collected through observation, interviews, questionnaires, and tests, then analyzed on cognitive, affective, and psychomotor aspects. The results of the study showed a significant increase: the average cognitive score increased from 56 in cycle I to 86 in cycle II, affective from 60 to 89, and psychomotor from 65 to 93, with classical learning completion increasing from 55% to 100%. It was concluded that the application of the Quantum Teaching method with pictorial and audiovisual media effectively improved the poetry writing ability of fourth-grade students of SDN 2 Blembem.